Kesan latihan motivasi terhadap komitmen kerja dalam kalangan pegawai kakitangan sokongan Majlis Perbandaran Johor Bahru Tengah (MPJBT) - Abdullah, Mohamad Samari (2014)
This study aims to identify the effect of training motivation towards work commitment among support staff in the Department of Management Services MPJBT. This research is the study of experimental design. The sample consisted of 60 respondents ie 30 people is made up of the control group and 30 the other is made up of the experimental group. The study involves two main variables of training motivation and work commitment dimensions of affective commitment (AC), continuence commitment (CC) and normative commitment (NC). In this study, the questionnaire used is Work Commitment Questionnaire (WCQ) developed by Meyer and Allen (1997). WCQ consists of 23 items. Test and retest analysis showed that the questionnaire has high reliability of 0.823. As for the items affective commitment (AC), continuence commitment (CC) and normative commitment (NC) is 0.8523, 0.7956 and 0.7397 respectively. The officers involved MPJBT support groups are selected in matched pairs design. Officers support group for the experimental group underwent four weeks of training motivation. The results were analyzed quantitatively. T-test analysis showed a significant difference in test scores between work commitments pre and post test, thus proving the positive effects of exercise motivation. Some officials support groups in the experimental group scored significantly higher than the control group. In addition, there are significant differences on the increased motivation among personnel training support group before and after they attend a motivational training program. This proves that this motivational training should be given attention in order to increase commitment among officials working in the support group. The results generally support the finding that exercise can increase the motivation to work commitments. This is further strengthened by the overall feedback received motivational training program of support group officer training. Mean score is very high at 4.66. The study is expected to assist the support group MPJBT increasing work commitments to improve organizational performance in their workplace.